RB-SR SYSTEMATICS OF VENDIAN-CAMBRIAN CLAYSTONES FROM THE EAST EUROPEAN PLATFORM: IMPLICATIONS FOR A MULTI-STAGE ILLITE EVOLUTION - Gorokhov I.M.; Turchenko T.L.; Melnikov N.N.; Kutyavin E.P.; Baskakov A.V.; Clauer N.; Pirrus E. (My University, 1994)
A combined mineralogical, chemical, morphological and Rb-Sr isotopic study of “blue clays” from the Lower Cambrian Lontova unit shows that these minerals contain three generations of illite. The oldest detrital 2M illite particles are typically round with sharp borders sometimes rolled up and have a minimum isotopic age of 722 ± 13 Ma. This generation of illite is mainly concentrated in the 0.6–2-μm size fractions of the samples. The second generation of illite is represented by well-crystallized lath-type particles of 0.1-μm size with an age of 533 ± 8 Ma considered to be the sedimentation age. Faulting and/or regional emergence during the Ordovician to Early Silurian time probably induced extensive circulations of subsurface waters which precipitated an additional <0.1-μm generation of low-temperature lath-type illite particles at ~ 430–480 Ma ago. The Precambrian-Cambrian boundary may be set at ~ 530 ± 10 Ma based on the data presented here.Leaching of different clay subfractions by ammonium acetate shows that illite particles of different generations crystallized in environments with different ratios. The varied environmental Sr isotopic ratios were, at least in part, due to local interactions between the interstitial waters and the sedimentary mass. Additionally, the initial ratios of the clay particles from argillaceous sedimentary rocks were mostly higher than that of marine Sr.
Keywords: Cambrian; Vendian; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская::Вендский